Menyiapkan Generasi Wirausaha Muda: Tips Bisnis Kreatif dan Penguatan Jiwa Kewirausahaan di SMK Ganesha Tama - Dwi Nur Apriliani; Evina Mutiara Pratiwi; Nur Rahmawati; Suci Lailatul Ramadhani; Nur Asih Triatmaja (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
This community service activity was conducted at SMK Ganesha Tama Boyolali with the main objective of disseminating knowledge and practical tips on entrepreneurship and starting a business among vocational high school students. The activity aimed to provide students with an understanding of basic entrepreneurial concepts, initial steps in establishing a small business, and key factors that influence entrepreneurial success. This program was based on the importance of preparing vocational students not only to become skilled workers but also to develop the readiness to act as independent entrepreneurs. Several problems were identified prior to the activity, including students’ limited knowledge about how to start a business, fear of taking entrepreneurial risks, and low motivation to pursue entrepreneurship at an early stage. The method used in this program was mentoring through a socialization approach, supported by interactive discussions and question-and-answer sessions. The results showed a significant improvement in students’ understanding of entrepreneurship concepts and their ability to develop feasible business ideas. Most students successfully created simple business plans aligned with community needs, such as technical services, design and drawing services, planning consultancy, and mock-up services. In addition, the activity positively influenced students’ attitudes and mindset by increasing their self-confidence in presenting business ideas before their peers. Overall, this outreach program effectively fostered entrepreneurial spirit, motivation, and readiness among students at SMK Ganesha Tama Boyolali to pursue independent business opportunities after graduation.